2013
DOI: 10.3390/md11072667
|View full text |Cite
|
Sign up to set email alerts
|

Production, Characterization, and Antioxidant Activity of Fucoxanthin from the Marine Diatom Odontella aurita

Abstract: The production, characterization, and antioxidant capacity of the carotenoid fucoxanthin from the marine diatom Odontella aurita were investigated. The results showed that low light and nitrogen-replete culture medium enhanced the biosynthesis of fucoxanthin. The maximum biomass concentration of 6.36 g L−1 and maximum fucoxanthin concentration of 18.47 mg g−1 were obtained in cultures grown in a bubble column photobioreactor (Ø 3.0 cm inner diameter), resulting in a fucoxanthin volumetric productivity of 7.96 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
217
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(241 citation statements)
references
References 35 publications
14
217
0
10
Order By: Relevance
“…This implies that the availability of phosphorous in 30% v/v POME does not limit the growth of P. tricornutum under our experimental conditions. This finding was supported by a previous study who reported that a high amount of external nitrate increased the fucoxanthin productivity, growth rate, and biomass production of P. tricornutum and Odontella aurita cultivated on a modified f/2 and a modified L1 medium, respectively (Xia et al 2013;McClure et al 2018). Furthermore, early nitrogen limitation reduced the fucoxanthin productivity of P. tricornutum cultivated on a modified f/2 medium (Alipanah et al 2015).…”
Section: Discussionsupporting
confidence: 79%
“…This implies that the availability of phosphorous in 30% v/v POME does not limit the growth of P. tricornutum under our experimental conditions. This finding was supported by a previous study who reported that a high amount of external nitrate increased the fucoxanthin productivity, growth rate, and biomass production of P. tricornutum and Odontella aurita cultivated on a modified f/2 and a modified L1 medium, respectively (Xia et al 2013;McClure et al 2018). Furthermore, early nitrogen limitation reduced the fucoxanthin productivity of P. tricornutum cultivated on a modified f/2 medium (Alipanah et al 2015).…”
Section: Discussionsupporting
confidence: 79%
“…Their highly structured mesoporous cell wall of amorphous silica can be incorporated directly into nanodevices or used for the bioencapsidation and delivery of molecules 7 . Furthermore, diatoms are coveted organisms in the pharmaceutical, cosmetic and food industries as a natural source of polyunsaturated fatty acids, pigments and antioxidants [8][9][10][11] . Diatoms can also be used as expression systems for recombinant proteins or biomaterials 12,13 .…”
mentioning
confidence: 99%
“…Indeed, OA contains EPA and other components such as anti-oxidants, especially fucoxanthin known for its beneficial effects (Maeda et al 2009, Xia et al 2013, Tan & Hou 2014. Indeed, fucoxanthin has been described as having anti-obesity, anti-diabetic and anti-inflammatory effects (Maeda et al 2009, Tan & Hou 2014.…”
Section: Discussionmentioning
confidence: 99%